Lake size and fish diversity determine resource use and trophic position of a top predator in high‐latitude lakes. Issue 8 (23rd March 2015) - Eloranta, Antti P.; Kahilainen, Kimmo K.; Amundsen, Per‐Arne; Knudsen, Rune; Harrod, Chris; Jones, Roger I.
Abstract: Prey preference of top predators and energy flow across habitat boundaries are of fundamental importance for structure and function of aquatic and terrestrial ecosystems, as they may have strong effects on production, species diversity, and food‐web stability. In lakes, littoral and pelagic food‐web compartments are typically coupled and controlled by generalist fish top predators. However, the extent and determinants of such coupling remains a topical area of ecological research and is largely unknown in oligotrophic high‐latitude lakes. We analyzed food‐web structure and resource use by a generalist top predator, the Arctic charr Salvelinus alpinus (L.), in 17 oligotrophic subarctic lakes covering a marked gradient in size (0.5–1084 km 2 ) and fish species richness (2–13 species). We expected top predators to shift from littoral to pelagic energy sources with increasing lake size, as the availability of pelagic prey resources and the competition for littoral prey are both likely to be higher in large lakes with multispecies fish communities. We also expected top predators to occupy a higher trophic position in lakes with greater fish species richness due to potential substitution of intermediate consumers (prey fish) and increased piscivory by top predators. Based on stable carbon and nitrogen isotope analyses, the mean reliance of Arctic charr on littoral energy sources showed a significant negative relationship with lake surface area, whereas the mean trophic position of Arctic charr, reflecting the lake food‐chain length, increased with fish species richness. These results were supported by stomach contents data demonstrating a shift of Arctic charr from an invertebrate‐dominated diet to piscivory on pelagic fish. Our study highlights that, because they determine the main energy source (littoral vs. pelagic) and the trophic position of generalist top predators, ecosystem size and fish diversity are particularly important factors influencing function and structure of food webs in high‐latitude lakes. Abstract : We explored food‐web structure and the resource use by a generalist top predator, the Arctic charr Salvelinus alpinus (L.), in 17 subarctic lakes. Using stable isotope and stomach content analyses, we found that lake size and fish species richness are particularly important factors determining the main energy pathway (littoral vs. pelagic) and food‐chain length in oligotrophic high‐latitude lakes.